التغذية والنمو العصبي في مرحلة الطفولة - حجاج, محمد الامين (جامعة الوادي - University of Eloued, 2022)
تعتبر المرحلة الجنينية ومرحلة الطفولة المبكرة من الفترات الحرجة لنمو الجهاز العصبي وخاصة الدماغ. فالاختلالات البُنيوية التي يمكن أن تحدث للدماغ خلال هذه الفترة قد لا يمكن الشفاء منها مستقبلا بالرغم من خاصية الليونة العصبية للدماغ. وقد تناولت عدة بحوث حديثة في مجال العلوم العصبية تأثير بعض العوامل مثل الأمراض والوراثة والانفعالات على النمو السليم للدماغ. تطرقت هذه الدراسة إلى تأثير الغذاء وبعض العناصر الكيميائية الأساسية (المعادن، البروتينات، الفيتامينات) على نمو الدماغ في الفترة الجنينية وفترة الطفولة وتأثير ذلك على وظائف الدماغ في المدى الطويل والمستقبل الأكاديمي والمعرفي للطفل. كما تناولت الدراسة أهم مظاهر النمو العصبي في هذه الفترة الحاسمة. Abstract: The embryonic phase and early childhood are the most critical periods for the development of the nervous system, especially the brain. The structural abnormalities that could occur to the brain during this period may not be able to be cured in the future, despite the neural plasticity of the brain. Many recent studies in the field of neuroscience have tackled the effect of some factors such as diseases, genetics and emotions on the healthy development of the brain. The current study aims to investigate the effect of food and some basic chemical elements (minerals, proteins, vitamins) on brain development in the embryonic and childhood period. Also, it focuses on their impact on the brain functions in the long term and the child's academic and cognitive future. The study also dealt with the most important manifestations of neurodevelopment in this crucial period
مقال
Keywords: نمو الدماغ – الغذاء – الفترة الجنينية – العناصر الكيميائية - الطفولة; brain development - food - embryonic phase - chemical elements - childhood